2003
DOI: 10.1161/01.cir.0000065220.70220.f7
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein in Hypercholesterolemic Human Plasma Induces Vascular Endothelial Cell Apoptosis by Inhibiting Fibroblast Growth Factor 2 Transcription

Abstract: Background-Apoptosis of vascular endothelial cells (ECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
182
2
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(202 citation statements)
references
References 39 publications
8
182
2
7
Order By: Relevance
“…Therefore, these findings imply that cellular senescence may mediate endothelial dysfunction and atherogenesis after chronic exposure to a sublethal level of L5. In other studies, we have shown that the concentration of L5 is less than 10 μg/ml in healthy individuals and is 100 μg/ml in patients with acute myocardial infarction (Chan et al., 2013), 20 μg/ml in patients with chronic kidney disease (Chang et al., 2013, 2016), and 100 μg/ml in patients with hypercholesterolemia (Chen et al., 2003). These estimations indicate that the concentration of L5 chosen for our in vitro experiments is the same order of magnitude as the concentration detected in humans, suggesting that our findings may be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, these findings imply that cellular senescence may mediate endothelial dysfunction and atherogenesis after chronic exposure to a sublethal level of L5. In other studies, we have shown that the concentration of L5 is less than 10 μg/ml in healthy individuals and is 100 μg/ml in patients with acute myocardial infarction (Chan et al., 2013), 20 μg/ml in patients with chronic kidney disease (Chang et al., 2013, 2016), and 100 μg/ml in patients with hypercholesterolemia (Chen et al., 2003). These estimations indicate that the concentration of L5 chosen for our in vitro experiments is the same order of magnitude as the concentration detected in humans, suggesting that our findings may be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma LDL was isolated from patients with metabolic syndrome using sequential potassium bromide density‐gradient ultra‐centrifugation (density = 1.019–1.063 g/ml) and supplemented with protease inhibitor cocktail, 1% penicillin/streptomycin/neomycin mixture, and 0.5 mM EDTA. Isolated LDL was separated into five subfractions (L1–L5) using an anion‐exchange fast‐protein liquid chromatography system (GE Healthcare, Princeton, NJ, USA), as described previously (Chen et al., 2003). The bioactivity of each batch of L5 was determined by examining its ability to induce endothelial cell apoptosis in 24 hr (Chen et al., 2003).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The biological effects of ox-LDL are likely to depend on the oxidation level of the LDL. 22 Local further oxidation of ox-LDL by ROS produced by chondrocytes could enhance LOX-1 expression in an autocrine or paracrine manner. Indeed, we have demonstrated that TNF-a-and IL-1b-induced ROS production by chondrocytes results in oxidative modification of LDL (data not shown).…”
Section: Discussionmentioning
confidence: 99%